Deletion of the African Swine Fever Virus Gen I196L in the Georgia2010 Isolate Genome Does Not Affect Virus Replication or Virulence in Domestic Pigs - Elizabeth Ramirez-Medina; Paul A. Azzinaro; Alyssa Valladares; Ediane Silva; Leeanna Burton; Leandro Sastre; Vivian O’Donnell; James J. Zhu; Douglas P. Gladue; Manuel V. Borca (Viruses)
African swine fever (ASF) is a lethal disease of domestic pigs that is currently challenging swine production in large areas of Eurasia and the Caribbean. The causative agent, ASF virus (ASFV), is a large, double-stranded, and structurally complex virus. The ASFV genome encodes for more than 160 proteins; however, the functions of most of them are still in the process of being characterized. Recently, ASFV gene I196L has been reported as being critically involved in disease production in domestic pigs. We report here that a recombinant virus derived from the Georgia 2010 isolate (ASFV-G) lacking the I196L gene, ASFV-G-∆I196L, had the same ability to replicate in primary cultures of swine macrophage and, when experimentally inoculated in pigs, produced a fatal form of the disease similar to that caused by the parental virulent ASFV-G. Therefore, deletion of the I196L gene does not significantly affect virus replication and virulence in domestic pigs of the ASFV Georgia 2010 isolate.